Water-based adhesive with matte matte effect and preparation method of water-based adhesive
By constructing a cross-linking composite of a metal organic framework containing amino groups and hollow silica, a modified matting agent was prepared, which solved the problem of the lack of matte matte surface of existing water-based polyurethane adhesives and achieved excellent matte matte effect of water-based adhesives.
Patent Information
- Application Number
- CN202411859216.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing water-based polyurethane adhesives lack the effect of matte matte surfaces, which leads to the reflection of the adhesive area easily in adhesive applications that require matte effect, affecting the appearance.
By constructing a cross-linking composite of a metal organic framework containing amino groups and hollow silica, a modified matting agent is prepared and physically blended with an aqueous polyurethane dispersion and an antifoaming agent is prepared to produce an aqueous adhesive with a matte matte surface effect.
The surface roughness of the adhesive layer after curing the water-based adhesive is achieved, forming an excellent matte matte effect, avoiding reflection at the adhesive and enhancing the overall beauty.
Smart Images

Figure CN119529739A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based adhesives, and particularly relates to a water-based adhesive with a matte surface effect and a preparation method thereof. Background Art
[0002] Water-based adhesives refer to a type of adhesive material that uses water as a solvent or dispersion medium. They are generally composed of water-based resin dispersions, additives, etc. If classified according to the type of water-based resin dispersion, water-based adhesives can be roughly divided into water-based acrylic adhesives, water-based polyurethane adhesives, water-based epoxy resin adhesives, etc. Among them, water-based polyurethane adhesives are widely used in the fields of footwear, furniture manufacturing, fabrics, etc. due to their many advantages such as being green, environmentally friendly, and highly applicable. However, the existing water-based polyurethane adhesives still have certain disadvantages that limit their actual application effectiveness. This is because most of the existing water-based polyurethane adhesives do not have a matte matte effect (the so-called matte matte refers to the low surface gloss of the adhesive layer of the water-based polyurethane adhesive after curing, which can present a soft and hazy visual experience), which makes it difficult to glue some items that already have a matte matte effect, which can easily cause "reflection" at the glued area after gluing, resulting in a sense of abruptness and is not conducive to overall beauty. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a water-based adhesive with a matte effect and a preparation method thereof. The present invention creatively uses 2-aminoterephthalic acid and ferric chloride hexahydrate as organic ligands and iron sources, respectively, to construct a metal organic framework containing amino groups, and then Hollow silica is synthesized by a method and surface modified with an amino coupling agent to prepare hollow silica containing an amino group. Subsequently, a compound with an epoxy terminal group and a methyl side group obtained by hydrosilylation of tetramethyldisiloxane and 3,4-epoxy-1-butene is used as a cross-linking agent to cause ring-opening bonding between the epoxy group and the amino group to achieve cross-linking and compounding of the metal organic framework and the hollow silica, thereby obtaining a modified matting agent, which is physically blended with an aqueous polyurethane dispersion and a defoaming agent to prepare a water-based adhesive having a matte effect.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A water-based adhesive with a matte effect is prepared from a water-based polyurethane dispersion, a defoaming agent and a modified matting agent.
[0006] As a preferred technical solution of the present invention, the mass ratio of the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent is 100:0.1-0.3:1-2.
[0007] As a preferred technical solution of the present invention, the waterborne polyurethane dispersion is directly purchased from the market.
[0008] As a preferred technical solution of the present invention, the defoaming agent is directly purchased from the market.
[0009] As a preferred technical solution of the present invention, the modified matting agent is prepared by the following steps:
[0010] Step A: 2-aminoterephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide are mixed at a mass ratio of 1-2:3-4:90-100 at room temperature with stirring for 30-60 minutes, and then hydrothermally reacted at 120-140° C. for 24 hours, naturally cooled to room temperature, filtered, and the filter residue is taken, washed with methanol, and finally vacuum dried at 60-80° C. until constant weight, to obtain component A;
[0011] Step B: adding 1 part by weight of hollow silica, 0.2-0.25 parts by weight of an amino coupling agent and 0.1 parts by weight of deionized water to 100 parts by weight of anhydrous ethanol, stirring and mixing at 60-70° C. for 6-8 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60-80° C. until constant weight, to obtain component B;
[0012] Step C: tetramethyldisiloxane, 3,4-epoxy-1-butene and platinum catalyst are mixed at a mass ratio of 1:5-6:0.3-0.5 at 45-50° C. for 6 hours, filtered, the residue is removed, and distilled to obtain component C;
[0013] Step D: Add 0.5-0.7 parts by weight of component A, 1 part by weight of component B and 0.2 parts by weight of component C to 100 parts by weight of dimethyl sulfoxide, then stir and mix at 70-80° C. for 24 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80° C. until constant weight, and the preparation is completed.
[0014] Furthermore, the hollow silica in step B is prepared by the following steps:
[0015] Add 80 parts by weight of anhydrous ethanol and 1-1.5 parts by weight of polyacrylic acid to 20-30 parts by weight of ammonia water with a mass fraction of 25-30%, and then stir and mix at room temperature for 10-15 minutes, then drop 10-12 parts by weight of ethyl orthosilicate while stirring, continue stirring for 4-6 hours after the dropwise addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60-80°C until constant weight, and the preparation is completed.
[0016] Preferably, the molecular weight of the polyacrylic acid is 5000.
[0017] Preferably, the dropping rate is controlled at 3-4 s / drop.
[0018] Furthermore, the amino coupling agent in step B is silane coupling agent KH-540.
[0019] Furthermore, the platinum catalyst in step C is directly purchased from the market.
[0020] Furthermore, the distillation in step C refers to distilling at 65-68° C. for 1 hour to remove volatiles.
[0021] A method for preparing a water-based adhesive with a matte effect, the preparation method comprising the following steps:
[0022] The preparation is completed by stirring the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent at a stirring speed of 800-1000 rpm at room temperature for 5-10 minutes.
[0023] A method for using a water-based adhesive with a matte effect, the method comprising the following steps:
[0024] Apply the water-based adhesive on the surface of the substrate, then bond it, then cure it at 50-60℃ for 4-6h, and finally leave it naturally at room temperature for 4-5 days.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention creatively uses 2-aminoterephthalic acid and ferric chloride hexahydrate as organic ligands and iron sources, respectively, to construct a metal organic framework containing amino groups, and then based on Hollow silica is synthesized by a method and surface modified with an amino coupling agent to prepare hollow silica containing an amino group. Subsequently, a compound with an epoxy terminal group and a methyl side group obtained by hydrosilylation of tetramethyldisiloxane and 3,4-epoxy-1-butene is used as a cross-linking agent to cause ring-opening bonding between the epoxy group and the amino group to achieve cross-linking and compounding of the metal organic framework and the hollow silica, thereby obtaining a modified matting agent, which is physically blended with an aqueous polyurethane dispersion and a defoaming agent to prepare a water-based adhesive having a matte effect.
[0027] (2) The present invention creatively prepares a modified matting agent, which gives the water-based adhesive a matte effect. Compared with the prior art that directly uses spherical silica as a matting agent, the modified matting agent of the present invention can obtain a rougher surface structure by virtue of the metal organic framework with a polyhedral morphology, and the corresponding matte effect is also better. At the same time, since the cross-linking agent with a side group of methyl is used to crosslink the metal organic framework and the hollow silica (the present invention is based on the Stöber method to synthesize the hollow silica, firstly, polyacrylic acid is dissolved in a mixed system of ammonia water / anhydrous ethanol to form Colloidal aggregates, and then the dropped ethyl orthosilicate is hydrolyzed on the surface of the colloidal aggregates to generate silicon dioxide, which is subsequently washed to remove the internal colloidal aggregates and dried to obtain the obtained product) for cross-linking and compounding. Therefore, the prepared modified matting agent has low surface energy and can, to a certain extent, migrate to the surface spontaneously by utilizing the difference in surface tension during the curing process of the water-based adhesive, thereby better forming a rough surface structure. In addition, the hollow silica also greatly reduces the resistance during migration. Finally, through the synergistic effect of many aspects, the cured adhesive layer has an excellent matte and foggy effect.
[0028] (3) Based on the principle of matte surface, the present invention makes the surface roughness of the adhesive layer of the prepared water-based adhesive after curing higher and better unevenness. By adding a small amount of modified matting agent, an excellent matte surface effect can be obtained. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] The sources of the raw materials are as follows: water-based polyurethane dispersions were purchased from Anhui Dawei Huatai New Material Technology Co., Ltd., the product name is cationic water-based polyurethane dispersion AH-0201C, and the solid content (%) is 45±1%; defoamers were purchased from BYK, Germany, model BYK-025 defoamer; platinum catalysts were purchased from Shaanxi Ruike New Materials Co., Ltd., and the product name is platinum carbon.
[0031] Example 1
[0032] A water-based adhesive with a matte effect is prepared from a water-based polyurethane dispersion, a defoaming agent and a modified matting agent.
[0033] The mass ratio of the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent is 100:0.1:1.
[0034] The modified matting agent is prepared by the following steps:
[0035] Step A: 2-aminoterephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide were mixed at a mass ratio of 1:3:90 at room temperature with stirring for 30 minutes, and then hydrothermally reacted at 120° C. for 24 hours, naturally cooled to room temperature, filtered, and the filter residue was taken, washed with methanol, and finally vacuum dried at 60° C. until constant weight, to obtain component A;
[0036] Step B: Add 1 part by weight of hollow silica, 0.2 parts by weight of an amino coupling agent and 0.1 parts by weight of deionized water to 100 parts by weight of anhydrous ethanol, and then stir and mix at 60° C. for 6 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60° C. until constant weight, to obtain component B;
[0037] Step C: tetramethyldisiloxane, 3,4-epoxy-1-butene and platinum catalyst were mixed at a mass ratio of 1:5:0.3 at 45° C. for 6 hours, filtered, the residue was removed, and distilled to obtain component C;
[0038] Step D: Add 0.5 parts by weight of component A, 1 part by weight of component B and 0.2 parts by weight of component C to 100 parts by weight of dimethyl sulfoxide, then stir and mix at 70°C for 24 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60°C until constant weight, and the preparation is completed.
[0039] The hollow silica described in step B is prepared by the following steps:
[0040] Add 80 parts by weight of anhydrous ethanol and 1 part by weight of polyacrylic acid to 20 parts by weight of 25% ammonia water, then stir and mix at room temperature for 10 minutes, then add 10 parts by weight of tetraethyl orthosilicate dropwise while stirring, continue stirring for 4 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60°C until constant weight, and the preparation is completed.
[0041] The molecular weight of the polyacrylic acid is 5,000.
[0042] The dropping rate is controlled at 3s / drop.
[0043] The amino coupling agent in step B is silane coupling agent KH-540.
[0044] The distillation in step C refers to distilling at 65° C. for 1 h to remove volatiles.
[0045] A method for preparing a water-based adhesive with a matte effect, the preparation method comprising the following steps:
[0046] The preparation is completed by stirring the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent at a stirring speed of 800 rpm at room temperature for 5 minutes.
[0047] Example 2
[0048] A water-based adhesive with a matte effect is prepared from a water-based polyurethane dispersion, a defoaming agent and a modified matting agent.
[0049] The mass ratio of the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent is 100:0.3:2.
[0050] The modified matting agent is prepared by the following steps:
[0051] Step A: 2-aminoterephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide were mixed at a mass ratio of 2:4:100 at room temperature with stirring for 60 minutes, and then hydrothermally reacted at 140° C. for 24 hours, naturally cooled to room temperature, filtered, and the filter residue was taken, washed with methanol, and finally vacuum dried at 80° C. until constant weight, to obtain component A;
[0052] Step B: Add 1 part by weight of hollow silica, 0.25 parts by weight of an amino coupling agent and 0.1 parts by weight of deionized water to 100 parts by weight of anhydrous ethanol, and then stir and mix at 70° C. for 8 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 80° C. until constant weight, to obtain component B;
[0053] Step C: tetramethyldisiloxane, 3,4-epoxy-1-butene and platinum catalyst were mixed at a mass ratio of 1:6:0.5 at 50° C. for 6 hours, filtered, the residue was removed, and distilled to obtain component C;
[0054] Step D: Add 0.7 parts by weight of component A, 1 part by weight of component B and 0.2 parts by weight of component C to 100 parts by weight of dimethyl sulfoxide, then stir and mix at 80°C for 24 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 80°C until constant weight, and the preparation is completed.
[0055] The hollow silica described in step B is prepared by the following steps:
[0056] Add 80 parts by weight of anhydrous ethanol and 1.5 parts by weight of polyacrylic acid to 30 parts by weight of 30% ammonia water, then stir and mix at room temperature for 15 minutes, then add 12 parts by weight of ethyl orthosilicate dropwise while stirring, continue stirring for 6 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 80°C until constant weight, and the preparation is completed.
[0057] The molecular weight of the polyacrylic acid is 5,000.
[0058] The dropping rate is controlled at 4s / drop.
[0059] The amino coupling agent in step B is silane coupling agent KH-540.
[0060] The distillation in step C refers to distilling at 68° C. for 1 h to remove volatiles.
[0061] A method for preparing a water-based adhesive with a matte effect, the preparation method comprising the following steps:
[0062] The preparation is completed by stirring the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent at a stirring speed of 1000 rpm at room temperature for 10 minutes.
[0063] Example 3
[0064] A water-based adhesive with a matte effect is prepared from a water-based polyurethane dispersion, a defoaming agent and a modified matting agent.
[0065] The mass ratio of the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent is 100:0.2:1.8.
[0066] The modified matting agent is prepared by the following steps:
[0067] Step A: 2-aminoterephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide were mixed at a mass ratio of 1.5:3.5:95 at room temperature with stirring for 45 minutes, and then hydrothermally reacted at 130° C. for 24 hours, naturally cooled to room temperature, filtered, and the filter residue was taken, washed with methanol, and finally vacuum dried at 70° C. until constant weight, to obtain component A;
[0068] Step B: Add 1 part by weight of hollow silica, 0.23 parts by weight of an amino coupling agent and 0.1 parts by weight of deionized water to 100 parts by weight of anhydrous ethanol, and then stir and mix at 65° C. for 7 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 70° C. until constant weight, to obtain component B;
[0069] Step C: tetramethyldisiloxane, 3,4-epoxy-1-butene and platinum catalyst were mixed at a mass ratio of 1:5.5:0.4 at 48° C. for 6 hours, filtered, the residue was removed, and distilled to obtain component C;
[0070] Step D: Add 0.6 parts by weight of component A, 1 part by weight of component B and 0.2 parts by weight of component C to 100 parts by weight of dimethyl sulfoxide, then stir and mix at 75°C for 24 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 70°C until constant weight, and the preparation is completed.
[0071] The hollow silica described in step B is prepared by the following steps:
[0072] Add 80 parts by weight of anhydrous ethanol and 1.3 parts by weight of polyacrylic acid to 25 parts by weight of 27% ammonia water, then stir and mix at room temperature for 13 minutes, then add 11 parts by weight of tetraethyl orthosilicate dropwise while stirring, continue stirring for 5 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 70°C until constant weight, and the preparation is completed.
[0073] The molecular weight of the polyacrylic acid is 5,000.
[0074] The dropping rate was controlled at 3.5 s / drop.
[0075] The amino coupling agent in step B is silane coupling agent KH-540.
[0076] The distillation in step C refers to distilling at 66° C. for 1 h to remove volatiles.
[0077] A method for preparing a water-based adhesive with a matte effect, the preparation method comprising the following steps:
[0078] The preparation is completed by mixing the aqueous polyurethane dispersion, the defoamer and the modified matting agent at a stirring speed of 900 rpm at room temperature for 8 minutes.
[0079] Comparative Example 1
[0080] On the basis of Example 3, the modified matting agent was replaced by component A in an equal weight, and the rest remained unchanged.
[0081] Comparative Example 2
[0082] On the basis of Example 3, the modified matting agent was changed to component B in an equal weight, and the rest remained unchanged.
[0083] Comparative Example 3
[0084] Based on Example 3, component C in step D was replaced with an equal weight of dimethyl sulfoxide, and the rest remained unchanged.
[0085] Comparative Example 4
[0086] Based on Example 3, component C in step D was replaced with an equal weight of 2,2'-hexane-1,6-diyldioxirane, and the rest remained unchanged.
[0087] Comparative Example 5
[0088] On the basis of Example 3, the hollow silica in step B was changed to solid silica (purchased from Nanjing Jike Biotechnology Co., Ltd., product name is silica microspheres, item number is JK-04-001-060), and the rest remained unchanged.
[0089] Test Example 1
[0090] Gloss test:
[0091] The water-based adhesives prepared in Example 3 and Comparative Examples 1-5 were respectively coated on the surface of black glass, then cured at 60°C for 4 hours, and finally left naturally at room temperature for 5 days to form an adhesive layer with a thickness of 50 μm. The glossiness of 5 points of the adhesive layer was randomly measured at 60° using a gloss meter, and the average value was taken.
[0092] Table 1. Gloss test results
[0093] Glossiness / % Example 3 3.1 Comparative Example 1 10.4 Comparative Example 2 9.6 Comparative Example 3 8.2 Comparative Example 4 4.9 Comparative Example 5 6.0
[0094] From the comparison between Example 3 and Comparative Examples 1-5 in Test Example 1, it can be seen that the water-based adhesive prepared by the present invention has a lower gloss after curing, and the corresponding matte effect is also better.
[0095] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A water-based adhesive with a matte effect, characterized in that: The water-based adhesive is prepared from a water-based polyurethane dispersion, a defoaming agent and a modified matting agent.
2. The water-based adhesive with a matte effect according to claim 1, characterized in that: The mass ratio of the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent is 100:0.1-0.3:1-2.
3. The water-based adhesive with a matte effect according to claim 1, characterized in that: The modified matting agent is prepared by the following steps: Step A: 2-aminoterephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide are mixed at a mass ratio of 1-2:3-4:90-100 at room temperature with stirring for 30-60 minutes, and then hydrothermally reacted at 120-140° C. for 24 hours, naturally cooled to room temperature, filtered, and the filter residue is taken, washed with methanol, and finally vacuum dried at 60-80° C. until constant weight, to obtain component A; Step B: adding 1 part by weight of hollow silica, 0.2-0.25 parts by weight of an amino coupling agent and 0.1 parts by weight of deionized water to 100 parts by weight of anhydrous ethanol, stirring and mixing at 60-70° C. for 6-8 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60-80° C. until constant weight, to obtain component B; Step C: tetramethyldisiloxane, 3,4-epoxy-1-butene and platinum catalyst are mixed at a mass ratio of 1:5-6:0.3-0.5 at 45-50° C. for 6 hours, filtered, the residue is removed, and distilled to obtain component C; Step D: Add 0.5-0.7 parts by weight of component A, 1 part by weight of component B and 0.2 parts by weight of component C to 100 parts by weight of dimethyl sulfoxide, then stir and mix at 70-80° C. for 24 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80° C. until constant weight, and the preparation is completed.
4. The water-based adhesive with a matte effect according to claim 3, characterized in that: The hollow silica described in step B is prepared by the following steps: Add 80 parts by weight of anhydrous ethanol and 1-1.5 parts by weight of polyacrylic acid to 20-30 parts by weight of ammonia water with a mass fraction of 25-30%, and then stir and mix at room temperature for 10-15 minutes, then drop 10-12 parts by weight of ethyl orthosilicate while stirring, continue stirring for 4-6 hours after the dropwise addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60-80°C until constant weight, and the preparation is completed.
5. The water-based adhesive with a matte effect according to claim 4, characterized in that: The molecular weight of the polyacrylic acid is 5,000.
6. The water-based adhesive with a matte effect according to claim 4, characterized in that: The dropping rate is controlled at 3-4s / drop.
7. The water-based adhesive with a matte effect according to claim 3, characterized in that: The amino coupling agent in step B is silane coupling agent KH-540.
8. The water-based adhesive with a matte effect according to claim 3, characterized in that: The distillation in step C refers to distilling at 65-68° C. for 1 h to remove volatiles.
9. A method for preparing a water-based adhesive with a matte effect as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The preparation is completed by stirring the aqueous polyurethane dispersion, the defoaming agent and the modified matting agent at a stirring speed of 800-1000 rpm for 5-10 minutes.
Citation Information
Patent Citations
General preparation method of multistage porous metal organic framework material
CN113773517A
Scratch-resistant multi-layer composite matte film and preparation process thereof
CN116376427A
Preparation method of low-dielectric all-organic polyimide composite film for electronic packaging
CN116925399A
High-performance mildew-proof antibacterial matte beautifying edge-closing glue and preparation method thereof
CN118530691A
Benzene-free environment-friendly printable matt black adhesive tape and application thereof
CN118652640A